Long-Term Effect of Febuxostat on Endothelial Function in Patients With Asymptomatic Hyperuricemia: A Sub-Analysis of the PRIZE Study - Maruhashi, Tatsuya; Higashi, Yukihito; Yoshida, Hisako; Tanaka, Atsushi; Eguchi, Kazuo; Tomiyama, Hirofumi; Kario, Kazuomi; Kato, Toru; Oda, Nozomu; Tahara, Nobuhiro; Oguri, Mitsutoshi; Watada, Hirotaka; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Xanthine oxidase is involved in the production of uric acid and the generation of superoxide anion. We evaluated the long-term effect of febuxostat, a non-purine selective xanthine oxidase inhibitor, on endothelial function in patients with asymptomatic hyperuricemia. Methods: In the PRIZE study, patients with hyperuricemia were randomly assigned to either add-on febuxostat treatment (febuxostat group) or non-pharmacologic hyperuricemia treatment (control group). Among the 514 participants, endothelial function was assessed in 41 patients in the febuxostat group and 38 patients in the control group by flow-mediated vasodilation (FMD) of the brachial artery at the beginning of the study and after 12 and/or 24 months of treatment (63 men; median age, 68.0 years). Results: The least squares mean concentration of serum uric acid was significantly lower in the febuxostat group than in the control group at 6 months (mean between-group difference [febuxostat group - control group], -2.09 mg/dL [95% confidence interval (CI), -2.520 to -1.659]; P<0.001), 12 months (mean between-group difference, -2.28 mg/dL [95% CI, -2.709 to -1.842]; P<0.001), and 24 months (mean between-group difference, -2.61 mg/dL [95% CI, -3.059 to -2.169]; P<0.001). No significant differences were found between groups in the least squares mean estimated percentage change in FMD at 12 months (mean between-group difference, -0.56% [95% CI, -1.670 to 0.548]; P=0.319) and at 24 months (mean between-group difference, -0.60% [95% CI, -1.886 to 0.685]; P=0.357). Conclusions: Febuxostat treatment did not alter endothelial function assessed by FMD during a 2-year study period in patients with asymptomatic hyperuricemia.